Double stimuli-responsive polysaccharide block copolymers as green macrosurfactants for near-infrared photodynamic therapy. Issue 6 (21st January 2019) - Breitenbach, Benjamin B.; Steiert, Elena; Konhäuser, Matthias; Vogt, Lea-Marie; Wang, Yujen; Parekh, Sapun H.; Wich, Peter R.
Abstract : The NIR absorbing photosensitizer phthalocyanine zinc (PC(Zn)) was stabilized in aqueous media as water-dispersible nanoparticles with a reduction- and pH-responsive full polysaccharide block copolymer. Abstract : The NIR absorbing photosensitizer phthalocyanine zinc (PC(Zn)) was stabilized in aqueous media as water-dispersible nanoparticles with a reduction- and pH-responsive full polysaccharide block copolymer. A cellular uptake and also photo switchable intracellular activity of the cargo upon irradiation at wavelengths in the near infrared region were shown. The block copolymer was synthesized by applying a copper-free click strategy based on a thiol exchange reaction, creating an amphiphilic double-stimuli-responsive mixed disulfide. The dual-sensitive polysaccharide micelles represent a non-toxic and biodegradable green macrosurfactant for the delivery of phthalocyanine zinc. By encapsulation into micellar nanoparticles, the bioavailability of PC(Zn) increased significantly, enabling smart photodynamic therapy for future applications in cancer-related diseases.